2020
DOI: 10.1530/rep-19-0554
|View full text |Cite
|
Sign up to set email alerts
|

Hormonally controlled ILC antigen presentation potential is reduced during pregnancy

Abstract: Strategically located in mucosal barriers, innate lymphoid cells (ILCs) are relevant in local containment and tolerance of commensal microflora. ILCs have been recently described at the fetomaternal interface, where the development of a semi-allogeneic fetus can only succeed in a well-controlled immune environment. We postulate that ILCs adapt their antigen presentation capacity to protect pregnancy from excessive immune responses. Human ILCs were studied in deciduae of term pregnancies, peripheral blood and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Particularly, the antigen presentation capacity of ILCs has been found to be fundamental in immune homeostasis, as for instance in the gut [12,14]. During pregnancy, we have observed that the antigen presentation potential of ILCs is reduced [15]. This phenomenon may represent an adaptive mechanism involved in the tolerance against fetal antigens.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Particularly, the antigen presentation capacity of ILCs has been found to be fundamental in immune homeostasis, as for instance in the gut [12,14]. During pregnancy, we have observed that the antigen presentation potential of ILCs is reduced [15]. This phenomenon may represent an adaptive mechanism involved in the tolerance against fetal antigens.…”
Section: Introductionmentioning
confidence: 66%
“…Mononuclear cells were isolated as previously described [15]. Brie y, blood samples were centrifuged, serum discarded and cells were isolated by density centrifugation with Lymphoprep™ (STEMCELL Technologies Inc., Vancouver, Canada), following manufacturer's instructions.…”
Section: Human Samplesmentioning
confidence: 99%
“…ILC3s are among the innate immune cells that can traverse the placental barrier and may be vital in the defense against Toxoplasma gondii , which can be recognized by TLR2:1 [ 148 , 150 ]. In the presence of pregnancy-related factors and hormones in vivo in mice and in vitro in humans, ILCs display a reduced antigen presentation potential, evidenced by the lower expression of MHC II following inflammation [ 151 ]. This indicates that, during pregnancy, ILC functionality, in terms of antigen presentation, is redirected towards tolerance to support pregnancy [ 151 ].…”
Section: Apc Biology In Adult and Umbilical Cord Blood—what Is The Difference?mentioning
confidence: 99%
“…In the presence of pregnancy-related factors and hormones in vivo in mice and in vitro in humans, ILCs display a reduced antigen presentation potential, evidenced by the lower expression of MHC II following inflammation [ 151 ]. This indicates that, during pregnancy, ILC functionality, in terms of antigen presentation, is redirected towards tolerance to support pregnancy [ 151 ]. Currently, no data are available on the antigen presentation capabilities of UCB ILC populations and further studies by multiple laboratories are needed to identify the therapeutic potential of UCB-derived ILCs.…”
Section: Apc Biology In Adult and Umbilical Cord Blood—what Is The Difference?mentioning
confidence: 99%
“…Local and systemic immune adaptations facilitate the implantation and later the accommodation of the growing fetus (14)(15)(16)(17). These adaptations include the promotion of uterine vascular remodeling and the induction of immune tolerance (18)(19)(20)(21)(22)(23)(24). Both maternal lymphocytes and fetal derived cells including trophoblast establish a complex interaction to balance the inflammatory environment providing protection against pathogens and the necessary cytokine milieu that allows local structural modifications during placentation (17,25,26).…”
Section: Introductionmentioning
confidence: 99%